The Carbon-Nitrogen Balance of the Nodule and Its Regulation under Elevated Carbon Dioxide Concentration. (28th May 2014) - Libault, Marc
Abstract : Legumes have developed a unique way to interact with bacteria: in addition to preventing infection from pathogenic bacteria like any other plant, legumes also developed a mutualistic symbiotic relationship with one gender of soil bacteria: rhizobium. This interaction leads to the development of a new root organ, the nodule, where the differentiated bacteria fix for the plant the atmospheric dinitrogen (atmN2 ). In exchange, the symbiont will benefit from a permanent source of carbon compounds, products of the photosynthesis. The substantial amounts of fixed carbon dioxide dedicated to the symbiont imposed to the plant a tight regulation of the nodulation process to balance carbon and nitrogen incomes and outcomes. Climate change including the increase of the concentration of the atmospheric carbon dioxide is going to modify the rates of plant photosynthesis, the balance between nitrogen and carbon, and, as a consequence, the regulatory mechanisms of the nodulation process. This review focuses on the regulatory mechanisms controlling carbon/nitrogen balances in the context of legume nodulation and discusses how the change in atmospheric carbon dioxide concentration could affect nodulation efficiency.